The Silicon Valley-Hsinchu Connection: Technical Communities and Industrial Upgrading. - Saxenian, AnnaLee (Berkeley Planning Journal, 2001)
Silicon Valley in California and the Hsinchu- Taipei region of Taiwan are among the most frequently cited ‘miracles’ of the information technology era. The dominant accounts of these successes treat them in isolation, focusing either on free markets, multinationals or the state. This paper argues that the dynamism of these regional economies is attributable to their increasing interdependencies. A community of US-educated Taiwanese engineers has coordinated a decentralized process of reciprocal industrial upgrading by transferring capital, skill, and know-how and by facilitating collaboration between specialist producers in the two regions. This case underscores the significance of technical communities and their institutions in diffusing ideas and organizing production at the global as well as the local level. Reprinted by permission of the publisher.